THE PERFORMANCE IMPROVEMENT STRATEGY: KNOWLEDGE SHARING AND CAPABILITY ANALYSIS THROUGH EMPLOYEE ENGAGEMENT IN EMPLOYEES - Wiwin Riza Kurnia; Budi Santoso; Nurul Qomariah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of Knowledge Sharing and capabilities on the performance of Jember Regency Bawaslu employees, with Employee Engagement as an intervening variable. The background of this research departs from the importance of increasing the effectiveness of election supervision which requires technical skills, collaboration, and emotional attachment of employees to the organization. This study uses an explanatory quantitative approach with a survey method through a questionnaire distributed to all employees of the Jember Regency Bawaslu. Data analysis was carried out using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique to test the direct and indirect relationships between variables. The results of the study show that Knowledge Sharing and capabilities have a positive and significant effect on Employee Engagement and employee performance. In addition, Employee Engagement has been proven to have a significant effect on employee performance and partially mediates the relationship between Knowledge Sharing and capabilities on performance. These results confirm that the improvement of Bawaslu employee performance is highly dependent on the ability to share knowledge, individual competencies, and employee attachment to organizational values and goals. This finding confirms that the improvement in the performance of Bawaslu employees is influenced by the ability of individuals to share knowledge, mastery of competencies, and emotional attachment to work and organizations